2018
DOI: 10.1063/1.5021475
|View full text |Cite
|
Sign up to set email alerts
|

Auger-generated hot carrier current in photo-excited forward biased single quantum well blue light emitting diodes

Abstract: We report on measurements of the photo-modulated current-voltage and electroluminescence characteristics of forward biased single quantum well, blue InGaN/GaN light emitting diodes with and without electron blocking layers. Low intensity resonant optical excitation of the quantum well was observed to induce an additional forward current at constant forward diode bias, in contrast to the usual sense of the photocurrent in photodiodes and solar cells, as well as an increased electroluminescence intensity. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Both the geometry of the on-wafer LEDs and the measurement setup are described elsewhere. 29 The EQE measurements are described in the study by Espenlaub et al 30 and are reproduced here (Fig. 2) to show the lack of efficiency droop in these MBE grown LEDs.…”
supporting
confidence: 55%
“…Both the geometry of the on-wafer LEDs and the measurement setup are described elsewhere. 29 The EQE measurements are described in the study by Espenlaub et al 30 and are reproduced here (Fig. 2) to show the lack of efficiency droop in these MBE grown LEDs.…”
supporting
confidence: 55%
“…The main mechanism invoked besides Auger NR recombination is carrier escape from the active region. Experimental evidence was shown to be disputable [61,63] and theoretical support further discussed in the LED simulation section shows it to be negligible.…”
Section: Simulations Of the Abc Recombination Parametersmentioning
confidence: 95%
“…Then, theorists calculated the effects of indirect phonon-assisted mechanisms or of QW finite thickness [56][57][58][59], however, still with smaller values than measured ones, which led to continuing disputing the Auger mechanism with others mechanisms such as diminished IE due to carrier escape [53] or overshoot [60] from active regions (see Figure 6). However, the evidence for carriers escaping the active region relied on misleading interpretations of measurements: forward minority electron current in the LED top p-layer can be mistaken for escape current, whereas it is due to Auger electrons bypassing the EBL [61][62][63] (it is remarkable that although Vampola et al [61] concluded that both thermal escape and Auger-assisted electron overflow of electrons could explain his data, most authors citing this article use it as proof of thermal escape of electrons); reverse photocurrent under low bias has been mistaken as an NR recombination channel (for a full discussion of issues in optical measurements, see the study by David et al [49]).…”
Section: Experimental Evidence Of Directly Observable Disorder-inducementioning
confidence: 99%
“…Theoretical calculations [34] and experimental evidence [8], [9] confirm that the occurrence of Auger recombination will assist electron leakage, also known as direct carrier leakage. Auger recombination generates hot carriers that can be recaptured by the QWs or facilitate electron leakage outside the QWs, as has been found to occur in GaInAsP/InP double-heterostructure LEDs and lasers [35], InGaN/GaN QW(s) blue LEDs [7] and SQW blue LEDs [36].…”
Section: Introductionmentioning
confidence: 92%